Prevention, Diagnosis and Treatment of Skin Cancer - Lallas, Aimilios (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint includes a collection of up-to-date articles on epidemiology, prevention, diagnosis and treatment of melanoma, basal cell carcinoma, squamous cell carcinoma and Merkel cell carcinoma. It also includes items on the use of artificial intelligence for skin cancer diagnoses as well as the impact of new immunotherapies on patient's quality of life.